SPIRITUALITAS MASYARAKAT DALAM NOVEL JATISABA KARYA RAMAYDA AKMAL - Yulisetiani, Septi (Paramasastra, 2016)
This article discusses about presentation of spiritualitty the traditional society in Jatisaba novels by Ramayda Akmal. Spirituality was the core which is one reason that someone in entities do something. Spirituality also a top to be achieved by someone after do something.  Be spiritual means has ties more on this to be a chaplaincy and psychological compared with this to be physical and material. Meaning spirituality understood as a series of characteristic motivasional, the emotional common cause, direct and choose diverse mannerisms individuals. Individuals will try to building an understanding of goals and purport to live in. Spirituality open the door to expand understanding of motivation and goal individuals. Transdensi spiritual individual reflect the ability to stand erect build lives of sight more plural, with the realization and meaning deeper accompained purport to the purpose live in a relationship that more enduring; relationship with one God. The individual is a part comunity. Spirituality community to describe in this novels identified by a set of an idea or ideas related to the belief system. The belief system in perspective anthropology includes two things interconected, there are the system religious and religious ceremony.